Molecular structure and vibrational bands and chemical shift assignments of 4-allyl-5-(2-hydroxyphenyl)-2,4-dihydro-3H-1,2,4-triazole-3-thione by DFT and ab initio HF calculations - Karakurt, Tuncay; Dincer, Muharrem; Cetin, Ahmet; Sekerci, Memet (Pergamon-Elsevier Science Ltd, 2010)
The title molecule, 4-allyl-5-(2-hydroxyphenyl)-2,4-dihydro-3H-1,2,4-triazole-3-thione (C11H11N3OS), was synthesized and characterized by IR-NMR spectroscopy and single-crystal X-ray diffraction. The compound crystallizes in the monoclinic space group is P2(1)/c,a=9.0907(5)angstrom,b = 9.1288(7)angstrom, c= 13.6222(7)angstrom, alpha=90 degrees, beta=98.442(4), y=90 degrees and V=2683.7(6)angstrom(3),F(000)=488, D-x = 1.386 g/cm(3). In addition to the molecular geometry from X-ray experiment, the molecular geometry, vibrational frequencies, gauge including atomic orbital (GIAO) H-1 and C-13 chemical shift values of the title compound in the ground state have been calculated using the Hartree-Fock (HF) and density functional method (DFT/BLYP and DFT/B3LYP) with 6-31G(d) basis set. To determine conformational flexibility, molecular energy profile of the title compound was obtained by HF/6-31G(d) calculations with respect to selected degree of torsional freedom, which was varied from 180 degrees to +180 degrees in steps of 10 degrees. Besides, molecular electrostatic potential (MEP), frontier molecular orbitals (FMO), and several thermodynamic properties were performed by the HF and DRT methods. (c) 2010 Elsevier B.V. All rights reserved.
Keywords: X-ray structure determination; DFT; HF; NMR; IR spectra; Molecular electrostatic potential